1203 Sialendoscopy In Non-Stone Sialadenitis Is an Effective Therapeutic Approach. (12th October 2021) - Karia, R; Pepper, T; Ryba, F
Abstract: Introduction: The aim of this retrospective case series was to investigate the therapeutic effectiveness of salivary endoscopy for non-stone related sialadenitis and obstructive symptoms. Method: The records of 46 patients who underwent salivary endoscopy between September 2018 and December 2019 were reviewed. Included cases presented with at least one symptomatic major salivary gland, with no history or evidence of stone disease on clinical or radiologic examinations. Results: A total of 22 patients (48%) and 26 glands were identified. These patients had a mean age of 50.8 years (range 27–74) and 73% were female. Most cases (19/26) involved the parotid gland. The primary imaging modality used was ultrasound, with sialography reserved for suspected strictures. The most common sonographic finding was ductal dilation (50%). Dexamethasone was instilled at completion of sialendoscopy in 23/26 cases. Outcomes included symptomatic improvement in 15/18 patients (4 patients have follow-up pending) with 5/15 experiencing complete symptom resolution. 2/18 patients did not have any symptomatic improvement, and 1/18 experienced acute infection that was treated with antibiotics. No patients required gland excision. Conclusions: Salivary endoscopy is a minimally invasive and effective treatment for patients with non-stone sialadenitis that is refractory to conservative measures. Our review demonstrated 83% therapeutic benefit with gland preservation in all patients.